2000
DOI: 10.1093/geront/40.2.228
|View full text |Cite
|
Sign up to set email alerts
|

Social Contact, Socioeconomic Status, and the Health Status of Older Malaysians

Abstract: We tested the applicability of the stress buffering hypothesis in a developing country setting with data from the Senior Sample of the Malaysian Family Life Survey-2. Using ordered logistic regression methods, we examined whether having daily contact with adult children moderates the effect of low socioeconomic status (SES; conceptualized as a chronic stressor) on self-assessed health status. We found that low SES is associated with poorer health for all three ethnic groups--Malay, Chinese, and Indian. Further… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
45
0
2

Year Published

2004
2004
2021
2021

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 52 publications
(53 citation statements)
references
References 16 publications
6
45
0
2
Order By: Relevance
“…Wu and Rudkin (2000) found that low socioeconomic status is associated with poorer health for all three ethnic groups -Malay, Chinese, and Indian, and family, household structure and kinship patterns vary across the three main ethnic groups. The Malay kinship system is generally bilateral, with some areas adhering to a matrilineal system in patterns of post-marital residence and inheritance.…”
Section: Introductionmentioning
confidence: 96%
See 2 more Smart Citations
“…Wu and Rudkin (2000) found that low socioeconomic status is associated with poorer health for all three ethnic groups -Malay, Chinese, and Indian, and family, household structure and kinship patterns vary across the three main ethnic groups. The Malay kinship system is generally bilateral, with some areas adhering to a matrilineal system in patterns of post-marital residence and inheritance.…”
Section: Introductionmentioning
confidence: 96%
“…Social contact is also important for positive health outcomes. Co-residence with any family member matters to the wellbeing of elderly (Wu and Rudkin 2000;Al-Kandari and Crews 2014). Children who co-reside with or live near ageing parents are able to provide a range of supportive services, including transfers of money and material goods, assistance with household chores, personal care, and companionship (Wu and Rudkin 2000;Khan 2014).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Isso significa que as respostas a esses itens foram variáveis ou controversas, ou seja, inesperadamente, pessoas com uma boa qualidade de vida se sentem sozinhas, ou não têm em quem confiar. Talvez esse fato possa ser explicado por uma característica relativamente comum entre os idosos, com ou sem patologias associadas, que é a solidão e depressão 28 . Não é raro, nessa faixa etária, a perda de pessoas próximas e entes queridos, incluindo o próprio parceiro e os filhos, que se casam ou saem de casa.…”
Section: Discussionunclassified
“…Isso faz com que, mesmo que sejam indivíduos ativos fisicamente, com um bom nível de saúde e participação na comunidade, se sintam sozinhos, ou não tenham em quem confiar, justificando a variabilidade das respostas nesses itens. Analisando isoladamente os dados obtidos pela avaliação dos idosos assintomáticos, observou-se novamente o item de número 9 ("Eu me sinto sozinho"), apresentando um padrão variável ou inesperado de respostas, o que também poderia ser explicado pelo isolamento ou depressão 28 . Ao analisar apenas os dados dos indivíduos portadores de hemiplegia e de doença de Parkinson, encontra-se, como item errático, apenas o item 5 ("Eu tomo remédios para dormir").…”
Section: Discussionunclassified